2008
DOI: 10.2133/dmpk.23.356
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ileal Epithelial P-Glycoprotein Dysfunction Induced by Ischemia/Reperfusion using in vivo Animal Model

Abstract: We presented the ischemia/reperfusion (I/R) model which can evaluate changes in P-glycoprotein (P-gp) function induced by lipid peroxidation using surgical-sutures connected with the spring balance. The superior mesenteric artery and vein was occluded by hanging itself using surgical-sutures connected with the spring balance for 60 min (ischemia), followed by reperfusion by cutting of sutures. To determine the hanging force of blood vessel during ischemia, treatment at the hanging force of 50g load, 100g load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…We have previously reported an in vivo intestinal I/R model that was produced using a spring scale and surgical sutures. [7][8][9] Briefly, the superior mesenteric artery and vein in rats were occluded by lifting them using surgical-sutures (Natsume No. 3) connected to a spring balance for 1 h (ischemia condition), before reperfusion was induced by cutting the sutures (reperfusion conditions).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously reported an in vivo intestinal I/R model that was produced using a spring scale and surgical sutures. [7][8][9] Briefly, the superior mesenteric artery and vein in rats were occluded by lifting them using surgical-sutures (Natsume No. 3) connected to a spring balance for 1 h (ischemia condition), before reperfusion was induced by cutting the sutures (reperfusion conditions).…”
Section: Methodsmentioning
confidence: 99%
“…In these reports, a correlation was found between the function of P-gp 1 h after reperfusion and the expression level of P-gp, but no such relationship was recognized 24 h after reperfusion. 7,8) It was suggested that this was due to functional abnormalities or abnormal localization of P-gp.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations